Management of capital, assets and liabilities in islamic banking and takaful institutions - Muhammad Ridhwan Ab. Aziz; Ram Al Jaffri Saad (UMK Press, 2019)
The book includes a range of topics such as Malaysian Islamic financial system, Islamic banking industry and capital structures, management of Islamic banking assets, islamic banking liabilities, profitability and performance of Islamic banking industry, takaful industry and capital structures, assets of takaful operator, liabilities of takaful operators, profitability of takaful operator as well as issues in islamic abnking and takaful industry.